Analisis Konflik Commognitive Dalam Collaborative Problem Solving - Nursandi, Mutiara; Zulfah; Putra, Kasman Edi (Jurnal PEKA (Pendidikan Matematika), 2025)
This study aims to analyze commognitive conflict in collaborative problem solving in high, medium, and low category subjects. The type of research used in this study is descriptive qualitative research. The place where this research was conducted was at SMA Negeri 1 Kuok. The subjects in this study were students of class XI IPA SMA Negeri 1 Kuok, consisting of six students with a purposive sampling technique. The data analysis techniques used in this study were data reduction, data presentation, and conclusions/verification. After the data was analyzed, the data was validated using triangulation techniques, namely by comparing the results of students' diagnostic test answers to test questions and interview results with the subjects. From the results of the analysis that had been carried out, it was found that commognitive conflict in collaborative problem solving in high ability subjects was minimal. While in ability subjects, commognitive conflict in collaborative problem solving occurred, but not in all commognitive indicators. However, in low category subjects, commognitive conflict occurred in almost all indicators. Factors that cause commognitive conflict in collaborative problem solving are due to internal factors such as the subject not being used to reading questions, the subject does not understand the contents of the question, the subject does not know the formula or solution strategy in solving the question, is not careful in working on the question, etc.